Monitoring Alloy Formation during Mechanical Alloying Process by X-Ray Diffraction Techniques - Kadir Masrom, Abdul; Md. Diah, Noraizam; Mustapha, Mazli; Harun, Zawati (Malaysian Journal of Science, 2002)
Mechanical alloying (MA) is a novel processing technique that use high energy impact ball mill to produce alloys with enhanced properties and microscopically homogeneous materials starting from various powder mixtures. Mechanical alloying process was originally developed to produce oxide dispersion strengthened nickel superalloys. In principal, in high-energy ball milling process, alloy is formed by the result of repeated welding, fracturing and rewelding of powder particles in a high energy ball mill. In this process a powder mixture in a ball mill is subjected to high-energy collisions among balls. MA has been shown to be capable of synthesizing a variety of materials. It is known to be capable to prepare equilibrium and non-equilibrium phases starting from blended elemental or prealloyed powders. The process ability to produce highly metastable materials such as amorphous alloys and nano-structured materials has made this process attractive and it has been considered as a promising material processing technique that could be used to produce many advanced materials at low cost. The present study explores the conditions under which aluminum alloys formation occurs by ball milling of blended aluminum and its alloying elements powders. In this work, attempt was made in producing aluminum 2024 alloys by milling of blended elemental aluminum powder of 2024 composition in a stainless steel container under argon atmosphere for up to 210 minutes. X-ray diffraction together with thermal analysis techniques has been used to monitor phase changes in the milled powder. Results indicate that, using our predetermined milling parameters, alloys were formed after 120 minutes milling. The thermal analysis data was also presented in this report.